The temporal pattern of creativity and implementation in teams - ROSING, Kathrin (Institutional Knowledge at Singapore Management University, 2018)
Two broad sets of activities underlie team innovation: the creation and the implementation of new ideas. Despite the prevalence of this distinction, the temporal dynamics of creativity and implementation in teams and their relation to successful team innovation are not well understood. Building on and integrating linear phase models and complexity perspectives on the innovation process, we propose a temporal pattern of creativity and implementation that is linked to team innovation. We examine this temporal pattern in a longitudinal study of 76 project teams. Results show that teams engage in creativity throughout the entire life cycle of team projects; however, innovative teams refrain from focusing on implementation in early time frames and increase their focus on implementation over the course of the project. Episodes of unconstrained creativity in early time frames of a project appear to be a critical factor for team innovation. Our research provides a foundation for future research on team innovation that explicitly considers the temporal interplay of creativity and implementation.